Understanding Disciplinary Perspectives about the Faculty of Education of Tribhuvan University - Dhungana, Jiwan (Dristikon: A Multidisciplinary Journal, 2022)
This paper has focused on understanding the disciplinary perspectives of FOE of TU to understand how it can be a center of excellence in the field of teacher education and educational research in the SAARC. The study was carried out by reviewing a range of literature books, articles, reports, and websites to explore the disciplinary perspectives of FOE. Further, the study has compared the FOE pro programs and SPPU. The study found that the FOE of TU, as cocomparedith FOE of SPPU, needs to be a true expert educational consultant for the nation, a mini-parliament for educational discussions, educational research and dissemination center, and a pedagogical innovation center. Further, FOE of TU needs to design competitive teacher's education programs for pre-primary to university level teachers, improving FOE’s course and program structure and attracting high-caliber students to FOE studies. It is only likely to be achieved when there will be three-dimensional visionary disciplinary leadership.